Women's Labours in the Caribbean - Johnson, Michele A. (Atlantis, 2007)
This paper argues that Caribbean societies have always depended on significant amounts of women's labour for their social, economic and cultural development. It describes how, even so, that work has been largely devalued and/or unrecognised except in contested ways.